2021
DOI: 10.1186/s40364-021-00305-9
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-associated fibroblasts: an emerging target for metastatic cancer

Abstract: Metastasis suggests a poor prognosis for cancer patients, and treatment strategies for metastatic cancer are still very limited. Numerous studies have shown that cancer-associated fibroblasts (CAFs), a large component of the tumor microenvironment, contribute to tumor metastasis. Stromal fibroblasts at metastatic sites are different from CAFs within primary tumors and can be termed metastasis-associated fibroblasts (MAFs), and they also make great contributions to the establishment of metastatic lesions and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 87 publications
(202 reference statements)
0
23
0
Order By: Relevance
“…The role of tumor stromal cells, particularly CAFs, in the induction of migration in carcinoma cells has been shown previously [29]. To study the potential of PFD in reducing invasive properties of carcinoma cells, we first co-cultured MCF7 carcinoma cells known as low-vimentin expressers with CAF-CM for 48 h and then treated cells with a low concentration of PFD (40 µM) for 72 h (Figure 4A).…”
Section: Pirfenidone Reduces the Migration Of Cafs And Carcinoma Cellsmentioning
confidence: 75%
“…The role of tumor stromal cells, particularly CAFs, in the induction of migration in carcinoma cells has been shown previously [29]. To study the potential of PFD in reducing invasive properties of carcinoma cells, we first co-cultured MCF7 carcinoma cells known as low-vimentin expressers with CAF-CM for 48 h and then treated cells with a low concentration of PFD (40 µM) for 72 h (Figure 4A).…”
Section: Pirfenidone Reduces the Migration Of Cafs And Carcinoma Cellsmentioning
confidence: 75%
“…Fibroblasts distributed in the metastatic site are called metastasis‐associated fibroblasts (MAFs), which promote angiogenesis and the formation of immunosuppressive microenvironment in pre‐metastatic niche. 138 The main difference between MAFs and primary tumor‐related fibroblasts is that MAFs have a stronger ability to inhibit the anti‐tumor effect of immune cells, which is reflected explicitly in the higher levels of CC motif chemokines ligand 2 (CCL2), CXCL12, and interferon‐related genes secreted by MAFs. 139 Additionally, in metastatic liver cancer and gastric cancer, it was found that the decrease of CD3+ infiltrating lymphocytes and the increase of TAM cells were related to the high levels of MAFs, partly due to the chemokine CXC receptor 4 (CXCR4) signal transduction in α‐smooth muscle actin (α‐SMA)+ MAFs.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…69 As presented earlier, immune cells (e.g., TAMs, Treg, and neutrophil), stromal cells (e.g., CAFs, MSCs, and TECs), chemokines, cytokines, and growth factors in TME, are involved in a complex crosstalk with tumor cells that affects tumor growth and metastasis. 69 , 79 , 138 , 406 Furthermore, recent studies have emphasized the role of autophagy, lipid metabolism, and lncRNA in tumor metastasis. 212 , 240 , 255 …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Except for immune cells, cancer-associated fibroblasts (CAFs) represent a dominant component of the tumor stroma and contribute significantly to the formation of the TME. CAFs can facilitate the malignant phenotype of tumor cells, reinforce therapy resistance, and modulate other tumor-infiltrating immune cells by depositing and remodeling the extracellular matrix, and secreting cytokines or direct cell–cell contact [ 14 ].…”
Section: Introductionmentioning
confidence: 99%